Traffic-related air pollutants (TRAP) in relation to respiratory symptoms among security guards - Muniandy Pravin; Abdul Aziz Nurhanim; Zainal Abidin Nur Balqishanis; Mohd Jamil Putri Anis; Ahnan Karthiga (E3S Web of Conferences)
Traffic-related air pollutants (TRAP) comprises emissions from moving vehicles and secondary pollutants formed in the atmosphere. Security guards are among the outdoor workers exposed to TRAP pollutants, mainly particulate matter 2.5 (PM2.5), which can lead to chronic respiratory diseases. Occupational lung disease is a significant health concern in Malaysia, which, relatively little research on respiratory issues among Malaysian security personnel. The objective of this study is to evaluate the exposure level of TRAP PM2.5 and respiratory symptoms among security guards. The study utilized environmental monitoring to assess the concentration of TRAP PM2.5 and a questionnaire adopted from the American Thoracic Society Division of Lung Diseases questionnaire (ATS-DLD-78A) was administered to eligible respondents to observe symptoms of cough, phlegm, wheezing, and shortness of breath. Approximately 45% of the respondents reported experiencing cough as a respiratory symptom when exposed to high levels of TRAP PM2.5. Factors of smoking status and the number of cigarettes smoked per day have been identified as potential risk factors correlated with respiratory symptoms. Given this, implementing job rotations for security guards could minimize their exposure to pollutants over the long term, rather than solely focusing on raising awareness about the proper use of personal protective equipment.